Catalyst-free activation of permanganate under visible light irradiation for sulfamethazine degradation: Experiments and theoretical calculation. (15th April 2021) - Zhang, Chen; Tian, Suhong; Qin, Fanzhi; Yu, Yali; Huang, Danlian; Duan, Abing; Zhou, Chengyun; Yang, Yang; Wang, Wenjun; Zhou, Yin; Luo, Hanzhuo
Highlights: Visible light shows synergistic effect with PM for SMT degradation. The generation of O2 − was notably enhanced under visible light irradiation. Mn (III) and O2 − are responsible for SMT removal. Experiments and DFT are creatively combined to explore the degradation mechanism. Abstract: In this study, visible light (VL) was adopted for permanganate (PM) activation without additional catalyst, where sulfamethazine (SMT) was selected as the probe compound. Experiment results showed that the VL/PM system can effectively degrade SMT through pseudo-first-order reaction kinetics. Influencing factors including PM dosage, solution pH, humid acid (HA) and coexisting anions (CO3 2−, SO4 2−, Cl − and NO3 − ) which affect SMT photo-degradation were also examined. Pyrophosphate (PP) had an inhibitory effect on SMT degradation due to the complexation of PP with Mn (III). Electron spin resonance (ESR) spectrometry and UV-Vis spectrophotometer proved that VL can activate PM to generate ·O2 − and Mn (III) reactive species. Furthermore, based on the active site prediction, intermediates identification and Density Functional Theory (DFT) calculation, two main degradation pathways involving SMT molecular rearrangement and cleavage of S–N bond were proposed. Moreover, the energy barriers of the two degradation pathways were also calculated. This study offers a novel approach for aqueous SMT removal and deepens our understanding of the degradation mechanism of SMT through DFT calculation, which hopes to shed light on the future development of VL/PM treatment. Graphical abstract: Image, graphical abstract